KERAGAMAN GENETIK, HERTTABILITAS DAN KORELASI BEBERAPA KARAKTER AGRONOMI PADA GALUR F2 HASIL PERSILANGAN KACANG HIJAU (Vigna radiata (L.) Wilczek) - Lukman Hakim (Research Center for Biology-Indonesian Institute of Sciences, 2010)
The F2 progenies of two crosses among three mungbean varieties were evaluated with their parents (Varsha, Park it and Local Belu)at Muara Experimental Station, Bogor during dry season of 2007. The experiment was conducted in a randomized complete block design with three replications. The seed of each F2 progenies and parents were planted in four rows of four meters long.Plant spacing was 40 x 20 cm, each will contained one plant. Among the character studies, days to maturity, seed yield per plant and plant height had the highest coefficient of variability, with the mean of 51.3%, 49.8%, and 49.2% respectively.Number of branches, pod length and number of seed per pod had the lowest coefficient of variability, and the mean were 19.1%, 18.8%, and 17.6%.The heritability estimates of nine agronomic characters studied ranged from IS.6 to 65.2%. Plant height and number of pods per planthad the highest heritability estimates with mean of 65.2% and 58.6% respectively for the two crosses. The mean heritabilityestimate for seeds yield per plant, pod length and number of seeds per pod were the lowest of 19.4%, 18.3% and 15.6% respectively. Based on the F2 data, selection of plant height and days to maturity had the highest expected genetic advance of 45.8 and 41.0%.The mean expected genetic advance for pod length and number of seeds per pod were the lowest of 19.4 and 17.4%.Correlation coefficient between grain yield with plant height, number of pods per plant and seed size were positively significant (r = 0.404, 0.613 and 0.422 respectively). Correlation coefficient between grain yield with other agronomic characters were small or negative. Therefore, plant height, number of pods per plant and seed size can be used as the selection criteria in selecting mungbean genotypes for high yield.